Muscle activity of the Lumbo-pelvic-hip complex in three isometric exercises using TRX ® rip trainer™ (Actividad muscular del complejo Lumbo-Pelvis-Cadera en tres ejercicios isométricos usando TRX® rip trainer™) - Andres Felipe Flores-Leon; Valeria Soto; Oscar Florencio Araneda; Rodrigo Guzman-Venegas; Francisco José Berral de la Rosa (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. One of the tools currently used for strengthening the lumbo-pelvic-hip complex (LPHC) is the TRX ® Rip Trainer™. This device produces asymmetric destabilizing forces by means of an elastic resistance (ER) cord. This study aimed to compare the level of muscle activity of LPHC, during the performance of three isometric exercises using TRX ® Rip Trainer™. Twenty-two healthy, physically active men (mean age 23 ± 2.35 years) were evaluated during the performance of “Drag” (anterior), "Drive" (posterior) and “Stack” (rotation) isometrically resisted exercises, performed using TRX ® Rip Trainer ™. The muscle activity of longissimus, external oblique, gluteus medius, and biceps femoris was recorded by means of surface electromyography. There were differences regarding the side of the ER location in most of the evaluated muscles (p <.05). In addition, a Friedman test revealed differences between the exercises in relation to the evaluated muscle (p<.05). Usually, Stack exercise produces a higher level of activity in these muscles. The findings of this study describe the behavior of LPHC muscles during the use of TRX ® Rip Trainer ™. Resumen. Una de las herramientas actualmente utilizadas para el fortalecimiento del complejo lumbo-pelvis-cadera (CLPC) es el TRX® Rip Trainer ™. Este dispositivo produce una fuerza desestabilizadora asimétrica por medio de un cordón de resistencia elástica (RE). Este estudio tuvo como objetivo comparar el nivel de actividad muscular de CLPC, durante la realización de tres ejercicios isométricos utilizando TRX® Rip Trainer ™. Veintidós hombres sanos, físicamente activos (edad media de 23 ± 2,35 años) se evaluaron durante la realización de los ejercicios de resistencia a la isometría “Drag” (anterior), "Drive" (posterior) y "Stack" (rotación), realizados con TRX® Rip Trainer ™. Mediante electromiografía de superficie, se registró la actividad muscular de longissimus, oblicuo externo, glúteo medio y bíceps femoral. Hubo diferencias en relación con el lado de la ubicación de RE, en la mayoría de los músculos evaluados (p <.05). Además, un test de Friedman reveló diferencias entre los ejercicios en relación con el músculo evaluado (p <.05). Por lo general, el ejercicio Stack produce un mayor nivel de actividad en estos músculos. Los resultados indicados en este estudio describen el comportamiento de los músculos CLPC durante el uso de TRX® Rip Trainer ™.